Karawitan Artwork “Semenanjung Senja” | Karya Karawitan “Semenanjung Senja” - I Putu Prabawa Laksana Putra (Pusat Penerbitan LPPMPP ISI Denpasar, 2023)
The moment when the sun sets and rises is a precious moment of God's beautiful grace. At this point, the composer put into a work entitled